Iklim Kerja Dan Gaya Kepemimpinan Terhadap Kinerja Karyawan - Rinda, Rachmatulailly Tinakartika; Bimo, Widhi Ariyo; Astria, Wiji (prodima@fe.uika-bogor.ac.id, 2016)
This study aims to determine how the influence of work climate and leadership style on employee performance in PT. Astro Makmur Sejahtera. The research method in the form of data collection is a questionnaire. The data analysis model used is multiple linear regression analysis. The sampling used in this study amounted to 60 respondents. In this study using the SPSS 25 for windows. With the results of the T test, namely the work climate variable, the tcount value is 0.835 < ttable 2.002 with a significance value of 0.407 > 0.05, these results can be concluded that H0 is accepted and Ha is rejected, which means that the work climate has no positive and insignificant effect. And the leadership style variable obtained tcount 3.059 > ttable 2.002 with a significance value of 0.003 <0.05, these results can be concluded that H0 is rejected and Ha is accepted, which means that leadership style has a positive and significant effect. While the results of the F test for work climate and leadership style variables obtained Fcount 21.118 > Ftable 3.16 with a significance value of 0.000 <0.05, these results can be concluded that H0 is rejected and Ha is accepted, which means that the work climate and leadership style have a positive and significant effect.